2015
DOI: 10.22256/pubvet.v5n31.1200
|View full text |Cite
|
Sign up to set email alerts
|

Relação sexual do parasitismo por Haemonchus contortus em Caprinos (Capra hircus)

Abstract: The hemoncose is an important parasitic disease to livestock, being the species sheep and goats the most affected. This disorder is caused by the nematode Haemonchus sp. abomasal parasite, measuring 1 to 2.5 cm. This is the most pathogenic helminthes, causing reduction of weight gain, severe anemia, edema of the gastric mucosa promoting decreasing the absorption of nutrients, external swelling called "edema of dewlap", and it’s characteristic signs of hemoncose, besides causing death in severe parasitosis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…Cardoso et al (2017) and Dias et al (2017) highlighted that the coccidia gender Eimeria are those who most affect the goats production in the world. Regarding the helminths found in the present study, it is noted that other previous works indicated the presence of Oesophagostumum sp., Haemoncus sp., and Strongyloides, as the parasites that most affect sheep and goats in the western Rio Grande do Norte, Brazil (AHID et al, 2008;FONSECA et al, 2011). Regarding the Kappa concordance values, among the studied techniques, it was observed that there was a moderated to strong concordance, therefore considered as similar (Table 3).…”
Section: Resultsmentioning
confidence: 97%
“…Cardoso et al (2017) and Dias et al (2017) highlighted that the coccidia gender Eimeria are those who most affect the goats production in the world. Regarding the helminths found in the present study, it is noted that other previous works indicated the presence of Oesophagostumum sp., Haemoncus sp., and Strongyloides, as the parasites that most affect sheep and goats in the western Rio Grande do Norte, Brazil (AHID et al, 2008;FONSECA et al, 2011). Regarding the Kappa concordance values, among the studied techniques, it was observed that there was a moderated to strong concordance, therefore considered as similar (Table 3).…”
Section: Resultsmentioning
confidence: 97%
“…Segundo Vieira (2007), os efeitos do parasitismo no rebanho se manifestam de várias formas, conforme as espécies presentes, a intensidade da infecção, a categoria e o estado fisiológico e nutricional do hospedeiro. O diagnóstico, de forma geral, é baseado em sinais clínicos, que na forma aguda apresentam perda de peso, diarreia, pelos arrepiados e sem brilho, anemia, desidratação e edema submandibular (FONSECA et al, 2011). A coprologia ajuda identificar a presença de ovos e larvas nas fezes (ROBERTO, 2018) e os achados na necropsia para verificar as lesões, assim como contagem de parasitos presentes no abomaso e outras espécies que possam acometer o hospedeiro (SCZESNY-MORAES et al, 2010).…”
Section: Haemonchus Contortusunclassified
“…Dessa forma, há aumento significativo na frequência de helmintoses gastrointestinais no rebanho nessas áreas para pastejo. Pastagens irrigadas podem influenciar na disponibilidade de L3, sendo encontradas larvas maciçamente no verão e em temperatura de 24°C (FONSECA et al 2011). Temperatura e umidade são fatores determinantes na sobrevivência das larvas em vida livre.…”
Section: Epidemiologiaunclassified